Ordinance No. 101: An Ordinance to Regulate the Discharge of Guns and Fireworks, in L.A. Civill, Charter of the City of Louisville, Ky.: Part Third, Ordinances of the City of Louisville 80 (1862) (enacted 1853) - (:unkn) unknown (My University, 1853)
Any person who shall discharge a gun, pistol, or other fire-arms, or any person, who shall set off a squib, cracker, or other fire works, in any public place, or send up a paper balloon or sky rocket, or throw a fire ball within the city, shall be fined four dollars.
Keywords: DISCHARGE